Innovation of the Platform Economy: Key Stakeholders and Starting Points for Sustainable Careers - Hofer, Annabelle; Rivkin, Wladislaw; Strich, Franz; Ihl, Andreas; Mayer, Anne-Sophie; Lei, Xue; Zhou, Lian; Huang, Xinran; Schweitzer, Vera M.; Genz, Sabrina; Gerten, Elisa; Trutwin, Lucas; et al. (Academy of Management Proceedings)
The platform economy introduces novel challenges and opportunities at the intersection of organizational structure, stakeholder relationships, and societal impact (Ashford et al., 2018; Caza et al., 2022; Cropanzano et al., 2023; Fieseler et al., 2019; Kuhn & Maleki, 2017). Following the call for rigorous methodological research on platform workers (Cropanzano et al., 2023), this symposium sheds light on the career development of platform workers by taking central stakeholders (e.g., workers, requesters, platform) into account. The five contributions cover diverse methodological approaches (e.g., longitudinal qualitative interviews, longitudinal quantitative surveys, diary studies), investigating online and offline platform workers from different online labor platforms (OLPs) in Asia, Europe, and the US. We bring together researchers from different fields (e.g., economics, management, psychology). They investigate how platform workers experience working on OLPs and how such experiences shape their careers. The symposium’s contributions collectively deepen our understanding of the platform economy by addressing platform design (cf. presentation [P] #P1, #P2), psychological aspects, such as well-being, linked to the interaction of workers with the requesters (cf. #P3), the decision-making of workers within the platform economy and its link to the gender pay gap (cf. #P4), and by proposing a novel framework of Transactional Careers to better understand the complex career development of platform workers (cf. #P5). This symposium will provide a platform for exchange among scholars from different fields interested in the platform economy to contributes substantial scientific implications for platform workers, policymakers, and OLPs for their important endeavor to develop a sustainable digitalized labor market, considering the role of different stakeholders.